Unbuild walls: why immigrant justice needs abolition - Shah, Silky (Haymarket Books, 2024)
"In the wake of post-9/11 xenophobia, Obama's record-level deportations, Trump's immigration policies, and the 2020 uprisings for racial justice, the US remains entrenched in a circular discourse regarding migrant justice. As organizer Silky Shah argues in Unbuild Walls, we must move beyond building nicer cages or advocating for comprehensive immigration reform. Our only hope for creating a liberated society for all, she insists, is abolition. Unbuild Walls dives into US immigration policy and its relationship to mass incarceration, from the last forty years up to the present, showing how the prison-industrial complex and immigration enforcement are intertwined systems of repression. Incorporating historical and legal analyses, Shah's personal experience as an organizer, as well as stories of people, campaigns, organizations, and localities that have resisted detention and deportation, Shah assesses the movement's strategies, challenges, successes, and shortcomings. Featuring a foreword by Amna A. Akbar, Unbuild Walls is an expansive and radical intervention, bridging the gaps between movements for immigrant rights, racial justice, and prison abolition." --